Consumption and social and demographic profile of the different household arrangements of the elderly in Brazil: analysis from the Study on Family Budgets - Natália Calais Vaz de Melo; Karla Maria Damiano Teixeira; Mirely Bonin Silveira (Revista Brasileira de Geriatria e Gerontologia, 2017)
Abstract Objective: to define the social and demographic profile of the different household arrangements involving the elderly, as well as to calculate the average annual consumption of such household arrangements according to the Pesquisa de Orçamentos Familiares (the Study on Family Budgets) (2008/2009). Method: a quantitative, descriptive, cross-sectional study was performed using secondary data extracted from the micro-data of the Study on Family Budgets (2008/2009), carried out by the Instituto Brasileiro de Geografia e Estatística (the Brazilian Institute of Geography and Statistics). In order to define the social and demographic profile of different household arrangements an exploratory analysis of the data was carried out, and the Gini index was used to identify if there was inequality in the distribution of consumption. Results: The results showed that elderly consumers can be seen as constituents of new generations, while most have only an elementary education and reside in an urban region of Brazil. There was a predominance of female heads of households in which there was no spouse present. When evaluating the distribution of the annual consumption of all the families, a greater weighting of the categories miscellaneous expenses, housing, transportation and food was found. Conclusions: Understanding the socioeconomic characteristics of the different home arrangements of the elderly, as well as their relationships with the consumption of goods and services, is extremely important, since the goods and services offered to this segment of the population can provide satisfaction with and improvement in quality of life.